Model Penanganan Ideologi Radikal Berdasar Komunikasi Efektif Orang Tua Anak, Peran Peer Group dan Konsep Diri - ADNJANI, MADE DWI; MUBAROK, MUBAROK (Universitas Muhammadiyah Yogyakarta, 2014)
Radical ideology is a latent threat that may arise any time. The spread of global radical ideology is aimed to the students who are members of Islamic student organizations. The characteristics of students which are open, easy to accept new things, critical, and having high spirit are used by many terrorist organizations to spread their radical ideology. The students who have already embedded radical ideology would be easy to commit terrorism actions such as murdering, kidnapping, robbing, and bombing. This research aims to determine the role of effective parentschildren communication, peer group, and selfconcept in neutralizing radical ideology which is followed by the students. In the short term, this research is expected to produce a model in handling radical ideology based on effective parents-children communication, the role of peer group, and self-concept. In the long run, this model is expected to prevent and neutralize radical ideology which is followed by the young generation so that they could be the successor of national struggle. Keywords: ideology, radicalism, communication